Fluconazole-Resistant Vulvovaginal Candidosis: An Update on Current Management - Karolina Akinosoglou; Achilleas Livieratos; Konstantinos Asimos; Francesca Donders; Gilbert G. G. Donders (Pharmaceutics)
Currently, the rising prevalence of resistant Candida species, particularly Candida albicans, as well as non-albicans isolates such as Candida glabrata and Candida krusei, represent challenges in their management. In this review, we aimed to explore the current management of fluconazole-resistant vulvovaginal candidiasis (FRVVC). Identified studies focused on alternative antifungal therapies, including boric acid, nystatin, and newer agents like oteseconazole and ibrexafungerp. The findings highlight the need for tailored treatment regimens, considering the variability in resistance patterns across regions. Unprofessional as well as professional overuse of antifungals for vulvovaginal symptoms that are not caused by Candida infections should be combatted and banned as much as possible. Instead of high-dose maintenance regimens using weekly doses of 150 to 200 mg of fluconazole for 6 months or longer, it is advisable to use an individualised degressive regimen (ReCiDiF regimen) in order to tailor the treatment of a particular patient to the lowest dosage possible to keep the diseases controlled. Additionally, this report underscores the impact of antibiotic use on the microbiota, which can raise the possibility of VVC and lead to fluconazole resistance, emphasizing the necessity for cautious antibiotic prescribing practices.